Real-Time IoT-Based Production Output Monitoring on High Pressure Die Casting Machine Using Patlite System - Muhammad Nashiruddin; Susanti Sundari (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
The aluminum High Pressure Die Casting process requires accurate real-time production monitoring to improve productivity, quality, and equipment efficiency. However, many die casting facilities still rely on manual production recording, causing reporting delays, recording errors, and limited operational visibility. This study develops an Internet of Things (IoT)-based production output monitoring system by integrating Patlite signals with a  DC350 High Pressure Die Casting machine. The system uses ESP32 microcontrollers, MQTT communication, and a web-based dashboard to automatically record machine status, shot count, production output, cycle time, downtime, and Overall Equipment Effectiveness (OEE). Experimental validation achieved 98.4% machine status detection accuracy, 99.2% production output accuracy, and 0.98-second communication latency. The system reduced manual recording time by 87%, improved production transparency and data reliability, and supported Industry 4.0 implementation in aluminum die casting manufacturing. Keywords: High Pressure Die Casting, Patlite, IoT, Production Monitoring, Smart Manufacturing